อนุพันธ์ ของฟังก์ชันประกอบ

$$ (gof)'(a) = g'(f(a)) \cdot f'(a)$$

พิสูจน์

\begin{align} & \cssId{Step1}{(gof)'(a) = \lim_{x \to a } \frac{ (gof)(x)-(gof)(a) } {x-a} } \\ &\cssId{Step2}{ = \lim_{x \to a } ( \frac{ g(f(x))-g(f(a)) } {x-a} )( \frac{f(x)-f(a)}{f(x)-f(a)} ) } \\ &\cssId{Step3}{ = \lim_{x \to a } (\frac{ g(f(x))-g(f(a)) } {f(x)-f(a) } )( \frac{f(x)-f(a)}{x-a} ) } \\ &\cssId{Step4}{ = \lim_{f(x) \to f(a) } \frac{ g(f(x))-g(f(a)) } {f(x)-f(a) } \cdot \lim_{x \to a } \frac{f(x)-f(a)}{x-a} } \\ &\cssId{Step5}{ =g'(f(a)) \cdot f'(a) } \end{align}